Investigation of wifi offloading behavior trade-off based on the quality of experience measurement - Ruliyanta (2024)
Global mobile data traffic is forecast to grow by 63 percent in 2016; at the country level, Indonesia leads the highest global growth at 142 percent. From the results of a 2017 survey released by the Indonesian Internet Service Providers Association, internet user penetration by city/district is concentrated in urban areas with a percentage of 72.41 %, rural-urban (49.49 %), and rural regions (48.25 %). The problem statement in this research is the lack of sufficient data on Wi-Fi offloading in Indonesia has prompted research into its socio-economic impacts. The study analyzes differences between economic strata, focusing on Wi-Fi usage patterns, network performance, and user behaviour. It aims to assess Wi-Fi performance through metrics like data usage, quality of service, and user experience, comparing these findings with manual survey data. The research objectives are to design a method for measuring Wi-Fi usage as a tool for conducting studies and to analyze network performance parameters, including end-to-end throughput and packet loss. Additionally, the study aims to measure QoE through user feedback and identify correlations between socio-economic groups in terms of Wi-Fi utilization patterns, network performance, and QoE Fairness Indexes. The methodology involves monitoring the internet usage patterns of volunteers who access office Wi-Fi. This study investigates the pattern of Wi-Fi offloading in the workplace. The goal is to see the effectiveness and pattern of using Wi-Fi in office buildings using 100 volunteers. The users are grouped into two groups; the first group is for workers with salaries according to government standards and is called the Socio 1 group, and the second group with a wage higher than the salary of Group 1 is called Socio 2. The survey results show that internet user penetration in Indonesia grew by 8 % to 143.26 million, or 54.68 % of the population. The most common internet usage is 1-3 hours daily, with popular activities including chat applications, social media, and video viewing. In Socio 1, average Wi-Fi usage is 2.88 hours per day with 4.2 GB of data, an 87.11 % QoS rate, and an 86.19 % QoE. In Socio 2, usage is 2.37 hours with 2.55 MB of data, a 92.45 % QoS rate, and a 91.36 % QoE.